Bubble Coarsening Kinetics in Porous Media. Issue 1 (29th December 2022) - Yu, Yuehongjiang; Wang, Chuanxi; Liu, Junning; Mao, Sheng; Mehmani, Yashar; Xu, Ke
Abstract: Bubbles in subsurface porous media spontaneously coarsen to reduce free energy. Bubble coarsening dramatically changes surface area and pore occupancy, which affect the hydraulic conductivity, mass and heat transfer coefficients, and chemical reactions. Coarsening kinetics in porous media is thus critical in modeling geologic CO2 sequestration, hydrogen subsurface storage, hydrate reservoir recovery, and other relevant geophysical problems. We show that bubble coarsening kinetics in porous media fundamentally deviates from classical Lifshitz‐Slyozov‐Wagner theory, because porous structure quantizes the space and rescales the mass transfer coefficient. We develop a new coarsening theory that agrees well with numerical simulations. We identify a pseudo‐equilibrium time proportional to the cubic of pore size. In a typical CO2 sequestration scenario, local equilibrium can be achieved in 1s for media consisting of sub‐micron pores, while in decades for media consisting of 1 mm pores. This work provides new insights in modeling complex fluid behaviors in subsurface environment. Plain Language Summary: In modeling fluid behaviors during geologic CO2 sequestration, hydrogen subsurface storage, hydrocarbon recovery and magma kinetics, the evolution of bubbles in subsurface porous media should be resolved to quantify hydraulic conductivity, mass and heat transfer coefficients, and reactional surface area. However, classical Lifshitz‐Slyozov‐Wagner theory qualitatively fails to predict bubbles' coarsening kinetics, as porous structure fundamentally reshapes the mass transfer pattern. A new coarsening theory is derived that perfectly matches numerical simulation. The evolution of free energy, pore occupancy, and surface area can be predicted, and an equilibrium time is identified that determines the validity of the local thermodynamic equilibrium presumption. This work helps to model complex fluid behaviors in many geophysical applications. Key Points: Bubbles in subsurface porous media coarsen toward equilibrium, which modifies local thermodynamics, transport, and reactive properties Classical Lifshitz‐Slyozov‐Wagner theory fails for bubbles coarsening in porous media, as porous geometry reshapes the concentration profile A new theory is derived that predicts the bubble population evolution during coarsening, which helps in modeling complex subsurface flow